Photocatalytic degradation of phenol using TiO2 nanocrystals supported on activated carbon - Carpio, Edward (2005)
It has been deposited titanium oxide on activated carbon (AC) in two forms as powder and as a pellet. This oxide was obtained using sol-gel process based on titanium isopropoxide and isopropyl alcohol. Nanocrystalline TiO2 anatase phase on activated carbon was obtained using an adequated thermal treatment of 325 °C by 5 h considering the thermal instability of the AC. The resulting material was characterized by spectroscopic X-ray fluorescence, scanning electron microscopy with energy dispersive X-ray microanalyses (EDX), and Brunauer–Emmett–Teller (BET) surface area measurements. Activity measurements performed under UV lamp and solar irradiations have shown good results for the photo degradation of phenol in aqueous solution. For solar applications, a polyethylene terephtalate bottle containing the photocatalyts was filled up with the contaminated water and place few hours under the solar radiation of a couple of sunny days. The results indicate that 20 ppm of phenol can be removed by using this method.